ANALYSIS OF THE RESULTS OF THE ACTIVITIES OF INSURANCE ENTERPRISES - Гладій, Ірина; Даценко, Ганна; Крупельницька, Ірина (SWorldJournal, 2023)
The article proves the necessity of conducting an analysis of the activities of insurance companies in modern business conditions in order to form a solvent, stable, competitive insurance market in Ukraine with proper protection of the rights of consumers